THE ROLE OF ENTREPRENEURIAL ENTITIES IN INCREASING UZBEKISTAN'S EXPORT POTENTIAL (KIUT Publication, 2025)
This article analyzes the role of small businesses and private entrepreneurship in enhancing the export potential of the Republic of Uzbekistan. Based on relevant statistical data, it highlights the share of entrepreneurial entities in total exports, their activities, and development trends. The study also examines key challenges in export operations, including limited financial resources, barriers to entering international markets, underdeveloped infrastructure, certification issues, logistics, and a shortage of skilled personnel. Recommendations for addressing these challenges are provided. The article contributes to a deeper understanding of reforms aimed at increasing the export potential of entrepreneurial entities.